Relasi Geometri dan Musik dalam Naskah Arsitektur Usmani Awal Abad ke-17 - Afiat Fahma Zamani; Asep Achmad Hidayat; Usman Supendi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
ABSTRACT. Historical records indicate that Islamic civilization is renowned for its grand architectural structures built by various dynasties throughout history. These structures reflect significant achievements in art, science, and engineering, showcasing a high level of architectural mastery. However, information about the architects behind these buildings is often limited. One rare historical document that provides insight into the memoirs of a notable architect from the Ottoman Empire is Risāle-i Miʿmāriyye by Cafer Efendi (died after 1633). This document discusses the development of Ottoman architecture in the early 17th century, including observations on the construction of the Sultan Ahmed Mosque. One of the topics covered in the treatise is the relationship between architectural structures based on geometric science and music. This article aims to reevaluate the level of geometric knowledge applied by Ottoman architect-engineers and artists, particularly Sedefkar Mehmet Ağa, by examining the linguistic and philosophical roots of geometric terms within the socio-cultural and architectural context of the time. The study investigates geometric shapes that produce acoustic effects in buildings through a critical analysis of the sixth section of Risāle-i Miʿmāriyye. The article reveals the complex relationship between the practice of geometric science and music at a specific time and place. The analysis indicates that the evolving connotations of vocabulary used to describe geometry and the various professionals working in the field reflect changes in the understanding of geometry and its application in architectural design. ABSTRAK. Dokumen sejarah telah mencatat bahwa peradaban Islam penuh dengan berbagai bangunan arsitektur megah yang dibangun oleh berbagai dinasti sepanjang sejarah. Struktur-struktur ini mencerminkan pencapaian besar dalam seni, ilmu pengetahuan, dan teknik, menunjukkan penguasaan yang tinggi dalam bidang arsitektur. Meski begitu, informasi mengenai arsitek di balik bangunan-bangunan ini sering kali terbatas. tidak banyak diketahui. Salah satu dokumen sejarah langka yang menuliskan memoar seorang arsitek kenamaan dari Kesultanan Usmani adalah Risāle-i Miʿmāriyye karya Cafer Efendi (meninggal setelah tahun 1633), yang membahas perkembangan arsitektur Usmani pada awal abad ke-17, termasuk pengamatan dalam proses konstruksi Masjid Sultan Ahmed. Di salah satu topik yang dibahas dalam risalah tersebut adalah hubungan antara struktur arsitektur berdasarkan ilmu geometri dan musik. Artikel ini bertujuan untuk mengevaluasi kembali tingkat pengetahuan geometri yang diterapkan oleh arsitek-insinyur dan seniman Usmani, Sedefkar Mehmet Ağa, dengan memeriksa akar linguistik dan filosofis dari istilah-istilah geometri dalam konteks sosial-budaya dan arsitektur pada saat itu. Studi ini menyelidiki bentuk-bentuk geometris yang menghasilkan efek suara dalam bangunan melalui analisis kritis terhadap bagian keenam dari Risāle-i Miʿmāriyye. Artikel ini mengungkap hubungan kompleks antara praktik ilmu geometri dan musik pada waktu dan tempat tertentu. Analisis menunjukkan bahwa konotasi kosakata yang berkembang untuk menggambarkan geometri dan para pengrajin profesional yang bekerja di bidang tersebut mencerminkan perubahan dalam pemahaman tentang geometri dan penggunaannya dalam desain arsitektur. Kata Kunci: Arsitektur Usmani, Risāle-i Miʿmāriyye, Geometri dan Musik.